Response to fungal exudates of the rhizosphere isolate Pseudomonas sp. UMAF110 involves a GGDEF/EAL domain-containing protein - Pintado Calvillo, Adrián; Aragón Cortés, Isabel María; Pérez-Martínez, Isabel; Pliego-Prieto, Clara; Crespo-Gómez, José Ignacio; De-Vicente-Moreno, Antonio; Cazorla-López, Francisco Manuel; Ramos-Rodríguez, Cayo Juan (My University, 2017)
Pseudomonas sp. UMAF110, isolated from rhizosphere soil in Spain, display in vitro antagonism towards the pythopathogenic fungus Rosellinia necatrix and is able grow in fungal exudates (BM-RE medium). A transposon mutant library of this strain was constructed and several mutants were selected by their reduced competitiveness in BM-RE medium. Pseudomonas sp. UMAF110-G3, which contains the transposon into a gene encoding a putative REC/PAS/GGDEF/EAL protein, was selected for further characterization. Blastn searches using the sequence of the gene interrupted by the transposon in UMAF110-G3, here called cmpA (c-di-GMP Metabolizing Protein), yielded a single positive hit (98% cover, 78% identity) with a gene from a terpene-degrading Pseudomonas sp. strain isolated from soil. Context analysis of the cmpA gene in Pseudomonas sp. UMAF110 showed that this gene is located downstream from several genes involved in flagellar motility/chemotaxis. RT-PCR experiments further confirmed that cmpA form a transcriptional unit with the che gene cluster. Expression analysis of cmpA by qRT-PCR clearly showed upregulation of this gene after transfer of Pseudomonas sp. UMAF110 cells to BM-RE medium, suggesting a role for this operon in response to fungal exudates. Deletion of cmpA in Pseudomonas sp. UMAF110 did not affect the ability of the strain to form biofilms under the conditions tested. However, overexpression of wild type CmpA in Pseudomonas putida KT2440 negatively regulated biofilm formation in this strain. Together, these results suggest that CmpA could be involved in signal transduction pathways regulating flagellar motility/chemotaxis in response to fungal exudates.
Keywords: Pseudomonas; Rhizosphere; Exudates; GGDEF/EAL